Role of Sociedad Peruana de Obstetricia y Ginecologia and Revista Peruana de Ginecologia y Obstetricia in the advances of the specialty, last 15 years - Pacheco Romero, José (2015)
Revista Peruana de Ginecologia y Obstetricia current Editorial Committee has been in charge of publishing the official medical journal of the Sociedad Peruana de Obstetricia y Ginecologia during the past 15 years. In this special paper, the Committee reviews the Journal’s publications between 1994 and 2008 and the coincident advances in the specialty, emphasizing the Sociedad Peruana de Obstetricia y Ginecologia’s role in this matter.